High tech migrant labor. - Nguyen, Alexander (American Prospect, 1999)
Information technology industry leaders contend that there is a shortage of skilled high-tech professionals and they are looking for more of the new class of migrant workers from India, the Philippines, China, and Taiwan to work in computer programming, software design, and information services. The technology firms want cheap foreign workers, but this approach treats immigrants as temps and undermines American job-seekers. The technology industries want to bring in more foreign workers through the H-1B visa program, which permits temporary guest workers to enter the country. However, this program depresses industry's incentive to retrain and hire American technology workers, especially older ones, who have a difficult time finding steady work in their fields. Furthermore, critics contend that the guest-worker program amounts to a back-door immigration policy, but it is a policy that separates human capital from the humans who provide it. Guest workers' labor is imported, but their potential citizenship is not acknowledged. Whereas legal resident status is attached to the immigrant, the H-1B visa is attached to the job.